Rivet-free lane-level combined ultra-high performance concrete pavement structure and preparation method thereof

By adopting rivetless composite bonding layer and high-performance concrete structure on the steel bridge deck, safety hazards and weak joints caused by rivet welding are solved, the overall durability and anti-slip capability of the bridge deck are improved, and driving is ensured. Comfort and safety.

CN119321089APending Publication Date: 2025-01-17JIANGSU SINOROAD ENG TECH RES INST CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411726242.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing steel bridge deck paving structure is prone to pores and burrs during the rivet welding process, resulting in safety hazards. The rivet setting increases the difficulty of later maintenance and maintenance, and the lane-level joints are weak links in the structure, which is prone to early damage and diseases, affecting the overall situation. Stable and durable structure.

Method used

Use rivetless composite bonding layer instead of traditional rivet point connection, combining ultra-high performance concrete, shear bonding layer and resin concrete functional wear layer, and form a waterproof and anti-corrosion protective layer through high tough resin and high-strength interface agent to enhance interlayer bonding and improve the toughness and crack resistance of the paved structure through composite rib mesh and fiber mesh.

Benefits of technology

Effectively avoid damage to the steel bridge deck by rivet welding, improve the overall anti-slip capability and waterproofness of the bridge deck, enhance the durability and crack resistance of the paving structure, ensure driving comfort and safety, and reduce The impact of bridge load.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119321089A_ABST
    Figure CN119321089A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of steel bridge deck pavement, in particular to a rivet-free lane-level combined ultra-high-performance concrete pavement structure and a preparation method thereof, and the rivet-free lane-level combined ultra-high-performance concrete pavement structure sequentially comprises a steel panel base layer, a rivet-free composite bonding layer, an unreinforced super-tough cement concrete pavement layer, a shear-resistant bonding layer and a resin concrete functional wearing layer from bottom to top. The ultra-high performance concrete serves as a pavement structure, overall deflection deformation of the bridge deck is reduced, and rigidity reinforcement is achieved. The resin gravel shear-resistant bonding layer effectively enhances the overall synergy and interface safety of the pavement structure through the dual effects of concave-convex surface physical occlusion and interface agent chemical bonding; by adopting the resin concrete functional wearing layer, the pavement flatness and the driving comfort and safety can be effectively improved, meanwhile, through cracks can be prevented from being generated by adopting the upper and lower step seams, and the trapezoidal tongue-and-groove seam structure increases interface bonding to guarantee the durability and usability of construction joints.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of steel bridge deck pavement, and in particular to a rivet-free lane-level combined ultra-high performance concrete pavement structure and a preparation method thereof. Background Art

[0002] With the rapid development of the economy, various bridges across the sea, across rivers, across rivers, railways, highways, etc. have been built in China. The scale of bridge construction in my country currently ranks first in the world. In the process of bridge design and construction, steel box bridges are widely used due to their advantages such as light weight, high torsional rigidity, and convenient construction. At the same time, ultra-high performance concrete is an ultra-high strength cement-based material with high strength, high durability, and low porosity. It has occupied an important position in the construction of my country's new century projects. Applying it to the pavement layer can significantly improve the bearing and crack resistance of the pavement structure, and increase its durability and service life.

[0003] The composite pavement structure is formed by combining structural layers of different material types and mechanical properties. This structure can make up for the shortcomings of rigid pavement, such as poor driving comfort and difficult maintenance. At the same time, it can also make the overall road surface stiff, stable and comfortable. The rivet welding process on the steel bridge deck will produce initial defects such as pores and burrs. These damages will cause great safety hazards to the steel bridge deck. At the same time, the setting of a large number of rivets will have a great impact on the subsequent maintenance and repair. Therefore, the rivet-free composite bonding layer can avoid the adverse effects of the rivet welding process on the steel bridge deck.

[0004] At present, since conventional concrete pavement is generally at the half-width or full lane section level, the use of the lane level involves the problem of adjacent joints. The joints are the weak link in the structure, and improper handling is prone to early damage and disease, affecting the overall structural stability and long-term durability. In addition, the steel bridge deck pavement is a pavement structure layer set on the steel bridge deck, which directly bears the high load of the bridge deck, high and low temperature environment and rain erosion. If the pavement is too thin, it cannot bear the load, and if it is too thick, it will increase the second-phase constant load of the bridge deck. Generally, the total pavement thickness is required to be 5 to 8 cm.

[0005] Therefore, how to set up a lane-level combined steel bridge deck pavement structure to reinforce the steel bridge deck and alleviate fatigue damage without using rivet welding, and adapt to different bridge deck pavement structures and requirements, is an urgent problem to be solved.

[0006] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0007] The technical problem to be solved by the present invention is as follows: to provide a rivet-free lane-level combined ultra-high performance concrete pavement structure and a preparation method, to reinforce the steel bridge deck and alleviate fatigue damage, to connect the steel bridge deck and the pavement structure with a rivet-free composite bonding layer to avoid the damage to the steel bridge deck caused by rivet welding in the prior art, to use ultra-high performance concrete as the main paving material to improve the durability of the pavement, to use a waterproof, pull-out and shear-resistant bonding layer that is synchronously cured with the concrete pavement to enhance the interlayer bonding performance, to use a composite reinforcement mesh and a fiber mesh to improve the toughness and crack resistance of the pavement structure, to use resin concrete as the upper pavement to ensure driving comfort, and to use a composite structure for the pavement structure to effectively reduce the bridge load.

[0008] The above technical objectives of the present invention are achieved through the following technical solutions:

[0009] A rivet-free lane-level composite ultra-high performance concrete pavement structure comprises a rivet-free composite bonding layer, a steel-free ultra-tough cement concrete pavement layer, a shear-resistant bonding layer and a resin concrete functional wear layer which are sequentially arranged on a steel panel base from bottom to top; the thickness of the lower concrete pavement of the composite pavement structure of the invention can be at least 3 cm, and the thickness of the upper resin concrete pavement can be at least 2 cm. The combination of the upper and lower pavements has a wider range of combinations to adapt to different bridge deck pavement structures and requirements.

[0010] Specifically, the structure adopts a rivet-free composite bonding layer "surface connection" instead of the traditional rivet "point connection" method, avoiding the thermal stress damage to the steel bridge deck and the concentrated stress phenomenon at the end of the rivet caused by conventional rivet 1200℃ welding. The high-toughness resin and high-strength interface agent used in the composite bonding layer can effectively bond with the steel plate to form an independent anti-corrosion and waterproof protective layer on the one hand, and slow solidification with the newly poured concrete on the other hand to reduce the interface shrinkage stress difference. Ultra-high performance concrete is used as a pavement structure to reduce the overall deflection deformation of the bridge deck to achieve stiffness reinforcement; the resin crushed stone shear bonding layer effectively enhances the overall coordination and interface safety of the pavement structure through the dual effects of physical biting of the concave and convex surfaces and chemical bonding of the interface agent; the use of a resin concrete functional wear layer can effectively improve the pavement flatness, driving comfort and safety, while the use of upper and lower step joints can prevent the occurrence of through cracks, and the trapezoidal tongue-and-groove joint structure increases the interface bonding to ensure the durability of the construction joint.

[0011] The joint between the unreinforced super-tough cement concrete pavement layer and the original pavement is constructed in the form of a tongue-and-groove joint. The unreinforced super-tough cement concrete pavement layer and the resin concrete functional wear layer are staggered with a spacing of 10 to 30 cm. The bevel of the tongue-and-groove joint avoids the wheel track position. The high-strength interface agent is applied to the construction joint interface with a coating amount of 0.2 to 1.6 kg / m 2The tongue-and-groove seam is designed to avoid unfavorable positions in the wheel track. The tongue-and-groove seam structure increases the interface area of ​​the seam and increases the bonding of the seam. Conventionally, the upper and lower layers are bonded with a layer of adhesive. The present invention uses resin + crushed stone + resin composite bonding to form an interface with a certain degree of roughness. Based on the dual effects of chemical bonding and physical bite, the shear resistance and bonding between the layers are increased.

[0012] Furthermore, the total thickness of the pavement structure is 5 to 9 cm, the thickness of the rivet-free composite bonding layer is 1 to 5 mm; the thickness of the unreinforced super-tough cement concrete pavement layer is 3 to 5 cm; the thickness of the shear-resistant bonding layer is 1 to 5 mm; and the thickness of the resin concrete functional wear layer is 2 to 5 cm.

[0013] As a preferred method, the thickness of the resin concrete functional wear layer is 2 cm, and the thickness of the unreinforced super-tough cement concrete pavement layer is 5 cm, which is composed of ultra-high performance concrete and composite bars. The composite bars include multiple longitudinal bars along the bridge and multiple transverse bars along the bridge. The longitudinal bars are arranged in the lower layer, and the transverse bars are arranged in the upper layer. The transverse and longitudinal spacing is 35 to 100 mm, and they are fixed by binding. The composite bars are basalt fiber bars, glass fiber bars or carbon fiber bars, with a diameter of 3 to 6 mm.

[0014] Furthermore, the rivet-free composite bonding layer is composed of high-toughness resin, crushed stone and high-strength interface agent; wherein the high-toughness resin is 1-2 kg / m 2 Evenly apply on the surface of the steel panel; the diameter of the crushed stone is 1-5mm, and the spreading amount is 3-5kg / m 2 ; High-strength interface agent coating amount 0.5~1.5kg / m 2 The time interval between coating and pouring of new concrete is 0.5 to 2 hours.

[0015] Furthermore, the high-toughness resin is composed of 40-60 parts of modified fatty amine curing agent, 40-60 parts of modified polyamide curing agent, and 1-2 parts of accelerator; the modified fatty amine curing agent is formed by heating reaction of 80-90 parts by weight of a first component and 10-20 parts by weight of a second component, the first component is an equal proportion of two of enamine, alkylamine or polyetheramine, and the second component is epoxy resin or active epoxy diluent.

[0016] Furthermore, the high-strength interface wet adhesive includes 70-80 parts of bisphenol A epoxy resin, 5-12 parts of ultrafine quartz powder, 5-8 parts of heavy-burned active calcium carbonate filler, 6-15 parts of polyester toughening agent, 10-18 parts of modified amine curing agent, 3-6 parts of liquid silica thixotropic agent, and 4-10 parts of propylene oxide phenyl ether diluent, wherein the particle size of the ultrafine quartz powder is 50-350μm, and the particle size of the heavy-burned calcium carbonate is 20-150μm.

[0017] Furthermore, the crushed stone is a single-grained stone with a size of 1 to 5 mm, which is obtained by mechanical crushing of basalt, diabase or andesite.

[0018] Furthermore, the unreinforced super-tough cement concrete pavement layer is composed of gel material, sand, coarse aggregate, water reducer, fiber, water, phase change material and chloride ion curing agent, wherein the gel material is 9-13 parts, sand is 8-12 parts, coarse aggregate is 4-9 parts, water reducer is 0.3-0.5 parts, fiber is 0.8-2.5 parts, water is 1.5-2 parts, phase change material is 0.3-0.6 parts, and chloride ion curing agent is 0.1-0.5 parts; the coarse aggregate includes crushed stone coarse aggregate and porous coarse aggregate, and the fiber is steel fiber or glass fiber or basalt fiber.

[0019] Furthermore, the tongue-and-groove joint is provided with a mortise and tenon by milling, the mortise and tenon is trapezoidal, the opening width is 800-1000mm, the bottom width is set to 400-600mm, and the mortise and tenon are spaced 1000-1200mm apart; the milling depth is 1.5-2.5cm, the exposed rate is 60%-70%, and the exposed rate of the steel fiber is 60%-75%.

[0020] Furthermore, the shear-resistant bonding layer is composed of high-toughness resin and crushed stone, and the coating amount of high-toughness resin is 1.2-2.5 kg / m 2 , crushed stone 2~4kg / m 2 Sprinkle evenly, cure for 2-4 hours, and apply high-toughness resin for the second time at 0.8-1.5kg / m 2 The coating time and the resin concrete construction time interval are 1 to 2 hours.

[0021] Further, the resin concrete functional wearing layer is composed of fine-graded dense resin concrete, polymer resin and wear-resistant aggregate particles;

[0022] The fine-graded dense resin concrete is composed of high-toughness resin adhesive, mineral aggregate, fiber and slow-release anti-icing agent; according to the ratio by weight, the high-toughness resin adhesive is 4-6 parts, the coarse aggregate is 75-87 parts, the fine aggregate is 5-10 parts, the slaked lime powder is 1-3 parts, the wearing layer fiber is 0.2-0.4 parts, and the slow-release anti-icing agent is 3-6 parts; the wearing layer mineral material is composed of steel slag coarse aggregate, limestone fine aggregate and slaked lime powder; the wearing layer fiber is flocculent polyester fiber or basalt fiber, and the fiber length is 10mm-30mm.

[0023] The polymer resin includes 75-85 parts of high-toughness resin, 10-15 parts of alicyclic polyamine curing agent, and 5-12 parts of anti-aging agent. The coating amount is controlled at 1-2 kg / m 2 ;

[0024] The wear-resistant aggregate is a mixture of 10 to 20 parts of oil-free steel slag, 15 to 35 parts of high-strength quartz sand, and 60 to 80 parts of basalt particles, with a particle size range of 1 to 5 mm.

[0025] A method for preparing a rivet-free lane-level combined ultra-high performance concrete pavement structure, calculated by mass fraction, comprises the following steps:

[0026] S1. The steel panel is sandblasted to remove rust and clean, and a steel panel base with a cleanliness level of Sa2.5 or above and a roughness of 60 to 150 μm is obtained;

[0027] S2. After sandblasting and rust removal, lay the rivet-free composite bonding layer within 3 hours, and evenly apply high-toughness epoxy resin on the surface of the steel panel at a dosage of 1-2 kg / m 2 ; Then spread the crushed stone with a diameter of 3 to 5 mm and a spreading amount of 3 to 5 kg / m 2 After curing for 12 to 24 hours, apply high-strength interface wet adhesive by manual rolling or mechanical spraying, with a coating amount of 0.5 to 1.5 kg / m 2 , forming a rivet-free composite bonding layer;

[0028] S3. Within 30 to 120 minutes after the high-strength wet bonding interface agent is applied, a non-reinforced super-tough cement concrete pavement layer is constructed, and a transverse and longitudinal composite reinforcement mesh is laid out, with longitudinal reinforcement arranged in the lower layer and transverse reinforcement arranged in the upper layer, with a transverse and longitudinal spacing of 35 to 100 mm, and fixed by binding. The composite reinforcement is basalt fiber reinforcement, glass fiber reinforcement or carbon fiber reinforcement, with a diameter of 3 to 6 mm;

[0029] The present invention provides cement concrete reinforced with steel bars in accordance with conventional requirements, thereby reducing the use of steel bars and maintaining the strength of the pavement structure.

[0030] S4. Prepare super-tough cement concrete according to the proportions of 9-13 parts of cementitious materials, 8-12 parts of sand, 4-9 parts of coarse aggregate, 0.3-0.5 parts of water reducing agent, 0.8-250 parts of steel fiber, 1.5-2 parts of water, 0.3-0.6 parts of phase change material, and 0.1-0.5 parts of chloride ion curing agent; pave the super-tough cement concrete on the rivet-free composite bonding layer, control the vibration interval to 0.5-1.0m, and the vibration time at each location to 10-20s. After vibration and compaction, perform surface calendering before initial setting, and perform milling on the surface after final setting to form tenons; the milling depth is 1.5-2.5cm, the exposed bone rate is 60%-70%, and the exposed steel fiber rate is 60%-75%, and then spray water mist and cover with film for moisturizing and curing for 14 days to form a high-density non-reinforced super-tough cement concrete pavement layer;

[0031] S5. After the maintenance of the unreinforced ultra-tough cement concrete pavement is completed, the floating slurry and loose debris on its surface are removed. There is a construction joint between the lane-level combined ultra-high performance concrete pavement and the original pavement. The upper and lower layers of the pavement are staggered, with a spacing of 10 to 30 cm, and a tongue-and-groove joint structure. The tongue-and-groove joint is set with a trapezoidal mortise and tenon groove by milling. The opening width is 800 to 1000 mm, the bottom width is set to 400 to 600 mm, and the distance between the mortise and tenon grooves is 1000 to 1200 mm. The high-strength interface agent is applied to the construction joint interface, and the coating amount is 0.2 to 1.6 kg / m 2 ;

[0032] S6. Then prepare a high-toughness, strong-bonding, long-lasting shear-resistant bonding layer; mix 40-60 parts of a modified fatty amine curing agent, 40-60 parts of a modified polyamide curing agent, and 1-2 parts of an accelerator to prepare a high-toughness resin; wherein the modified fatty amine curing agent is prepared by heating and reacting 80-90 parts by weight of at least two of enamine, alkylamine, and polyetheramine and 10-20 parts by weight of epoxy resin and at least one of an active epoxy diluent, and the coating amount is controlled to be 1.2-2.5 kg / m 2 , then 2~4kg / m 2 Spread the crushed stone evenly, and after curing for 2 to 4 hours, apply a second coat of high-toughness resin at 0.8 to 1.5 kg / m 2 ,

[0033] S7. Lay the resin concrete functional wear layer within 1 hour after the shear binder is applied. According to the weight ratio, the resin concrete is 4-6 parts, the coarse aggregate is 75-87 parts, the fine aggregate is 5-10 parts, the slaked lime powder is 1-3 parts, the polyester fiber is 0.2-0.4 parts, and the slow-release anti-icing agent is 3-6 parts; the wear layer mineral material is composed of steel slag coarse aggregate, limestone fine aggregate, and slaked lime powder. Stir at a speed of 50-70 rpm for 3-5 minutes at room temperature, spread evenly at a thickness of 2-5 cm, and compact it flatly for 8-10 times. After natural curing for 1 day, the resin concrete functional wear layer is paved.

[0034] In summary, the present invention has the following beneficial effects:

[0035] 1. The present invention coats high-toughness epoxy resin on the steel panel base and spreads crushed stone, and does not use traditional rivet welding to form a rivet-free composite bonding layer. The connection between the pavement layers is enhanced by the dual effects of physical bite and chemical bonding, so that the steel bridge deck and the pavement structure are integrated to deform under stress and improve the anti-slip ability between layers. The damage to the steel bridge deck caused by welding rivets in the prior art is eliminated. The present invention has good waterproof properties and super strong bonding properties, which can ensure that the entire bridge deck is impermeable and water-proof, and has a waterproof and anti-corrosion effect.

[0036] 2. Ultra-high performance concrete with added fiber and gel material is an important guarantee for the high strength of the pavement structure. The fiber improves the toughness of the concrete, and the composite reinforcement mesh laid can effectively improve the bending crack resistance of the pavement layer. At the same time, ultra-high performance concrete has the characteristics of high strength, good toughness and durability. Using it as a structural layer can improve the overall stiffness of the steel bridge deck system and play a reinforcing role.

[0037] 3. The present invention adopts resin concrete as the wearing layer, which can reduce vibration and noise, improve driving comfort and safety, and apply shear-resistant adhesive between the resin concrete wearing layer and the unreinforced super-tough cement concrete pavement layer to enhance the interlayer connection of the pavement and improve the durability of the pavement layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 Schematic diagram of the ultra-high performance concrete paving composite structure in an embodiment of the present invention.

[0040] Figure 2 It is a schematic diagram of the connection between the unreinforced super-tough cement concrete pavement layer and the original pavement structure in an embodiment of the present invention.

[0041] Figure 3 Schematic diagram of the connection between the unreinforced super-tough cement concrete pavement layer and the resin concrete functional wearing layer in an embodiment of the present invention.

[0042] Figure numbers: 0-steel panel base, 1-rivet-free composite bonding layer, 2-unreinforced super-tough cement concrete paving layer, 3-shear-resistant bonding layer, 4-resin concrete functional wear layer, 5-original pavement. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0044] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.

[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0046] In a specific embodiment of the present invention, the sources of various commercially available materials are as follows:

[0047] Components Commercial sources Modified polyamide curing agent Polyamide 651 curing agent Accelerator Vulcanization accelerator CBS (CZ) First component (enamine or alkylamine or polyetheramine) Cosmai T403 Second component (epoxy resin or reactive epoxy diluent) Huayu Polymer Emulsion New Park-Polyacrylamide Polyvinyl alcohol Sigma-Aldrich Cementitious materials Zhonglu New Materials sand Henan machine-made sand coarse aggregate Jiangsu Maodi Water reducing agent Subot-Polycarboxylic Acid Steel Fiber Suzhou Longyu Phase change materials Honeywell Phase Change Energy Storage Chloride Ion Curing Agent Xiaoxi E200 Resin concrete Zhonglu New Materials Coarse aggregate Jiangsu Maodi fine aggregate Jiangsu Maodi Slaked lime powder Granite powder Polyester Louis Da Slow-release antifreeze agent Zhonglu New Materials Bisphenol A epoxy resin NPEL-128 Ultrafine quartz powder Marine powder Dead-burned activated calcium carbonate filler Changxing Tianhe Polyester toughening agent WSG-930 Modified amine curing agent Rich Chemical Liquid Silica Thixotropic Agent LA-150 Propylene oxide phenyl ether diluent LS-692 High toughness resin Zhonglu New Materials Alicyclic polyamine curing agent WSG-322 Anti-aging agents WU-100

[0048] Example 1

[0049] like Figure 1 A rivet-free lane-level combined ultra-high performance concrete pavement structure is shown, with a total thickness of 6.6 cm, comprising a 3 mm rivet-free composite bonding layer 1, a 3.5 cm unreinforced ultra-tough cement concrete pavement layer 2, a 3 mm shear-resistant bonding layer 3 and a 2.5 cm resin concrete functional wear layer 4, which are sequentially arranged on a steel panel base 0 from bottom to top;

[0050] like Figure 2 and 3 As shown in the figure, there is a construction joint between the unreinforced super-tough cement concrete pavement layer 2 and the original pavement 5. The unreinforced super-tough cement concrete pavement layer 2 and the resin concrete functional wear layer 4 are staggered in the form of tongue-and-groove joints with a spacing of 15 cm. The bevel of the tongue-and-groove joint avoids the position of the wheel track. The high-strength interface agent is applied to the construction joint interface with a coating amount of 0.18 kg / m 2 .

[0051] A method for preparing a rivet-free lane-level combined ultra-high performance concrete pavement structure, calculated by mass fraction, comprises the following steps:

[0052] S1. The steel panel is sandblasted to remove rust and clean, and a steel panel base with a cleanliness level of Sa2.5 or above and a roughness of 120μm is obtained;

[0053] S2. After sandblasting and rust removal, lay the rivet-free composite bonding layer within 3 hours, and evenly apply high-toughness epoxy resin on the surface of the steel panel at a dosage of 1.2kg / m2 ; Then spread the gravel with a diameter of 3.5mm and a spreading amount of 4.2kg / m 2 , forming a rivet-free composite bonding layer; the high-toughness resin is composed of 52 parts of modified fatty amine curing agent, 45 parts of modified polyamide curing agent, and 1 part of accelerator; the modified fatty amine curing agent is formed by heating reaction of 85 parts by weight of a first component and 12 parts by weight of a second component, the first component is an equal proportion of two of enamine or alkylamine or polyetheramine, and the second component is an epoxy resin or an active epoxy diluent.

[0054] The high-strength interface wet adhesive is composed of 78 parts of bisphenol A epoxy resin, 8 parts of ultrafine quartz powder, 6 parts of heavy-burned active calcium carbonate filler, 6-15 parts of polyester toughening agent, 15 parts of modified amine curing agent, 4 parts of liquid silica thixotropic agent, and 7 parts of propylene oxide phenyl ether diluent. The ultrafine quartz powder has a particle size of 150μm and the heavy-burned calcium carbonate has a particle size of 50μm. After the rivet-free composite wet adhesive layer is cured for 12 hours, the high-strength interface wet adhesive is manually rolled or mechanically sprayed on it, with a coating amount of 0.8kg / m 2 ;

[0055] S3. Within 60 minutes after the high-strength wet bonding interface agent is applied, the non-reinforced super-tough cement concrete pavement layer is applied, and the transverse and longitudinal composite reinforcement mesh is arranged. The longitudinal reinforcement is arranged in the lower layer, and the transverse reinforcement is arranged in the upper layer. The transverse and longitudinal spacing is 50mm, and it is fixed by binding. The composite reinforcement is basalt fiber reinforcement, glass fiber reinforcement or carbon fiber reinforcement, with a diameter of 3.5mm. Then the non-reinforced super-tough cement concrete pavement layer can be poured;

[0056] S4. Prepare ultra-high performance concrete according to the proportion of 10 parts of cementitious material, 10 parts of sand, 5 parts of coarse aggregate, 0.35 parts of water reducer, 150 parts of steel fiber, 1.8 parts of water, 0.5 parts of phase change material, and 0.4 parts of chloride ion curing agent; pave the ultra-high performance concrete on the rivet-free composite bonding layer, control the vibration interval to 0.8m, and the vibration time at each location to 20s. After vibration and compaction, perform surface calendering before initial setting, and perform milling on the surface after final setting to form tenons; the milling depth is 2.0cm, the exposed bone rate is 65%, and the exposed rate of steel fiber is 70%, and then spray water mist and cover with film for moisturizing and curing for 14d to form a high-density non-reinforced ultra-tough cement concrete pavement layer;

[0057] S5. After the maintenance of the unreinforced ultra-tough cement concrete pavement is completed, the floating slurry and loose debris on its surface are removed. There is a construction joint between the lane-level combined ultra-high performance concrete pavement and the original pavement. The upper and lower layers of the pavement are staggered with a spacing of 15 cm and a tongue-and-groove joint structure. The tongue-and-groove joint is set with a trapezoidal mortise and tenon groove by milling. The opening width is 800-1000 mm, the bottom width is set to 500 mm, and the distance between the mortise and tenon grooves is 1100 mm. The high-strength interface agent is applied to the construction joint interface with a coating amount of 0.6 kg / m 2 ;

[0058] S6. Then prepare a high-toughness, strong-bonding, long-lasting shear-resistant bonding layer; mix 50 parts of a modified fatty amine curing agent, 50 parts of a modified polyamide curing agent, and 1.5 parts of an accelerator; wherein the modified fatty amine curing agent is formed by heating and reacting 86 parts by weight of at least two of enamine, alkylamine, and polyetheramine and 15 parts by weight of an epoxy resin and an active epoxy diluent, and the coating amount is controlled to be 1.6 kg / m 2 ;

[0059] S7. Lay the resin concrete functional wearing layer within 1 hour after applying the shear-resistant binder. The resin concrete functional wearing layer consists of fine-graded dense resin concrete, polymer resin and wear-resistant aggregate particles.

[0060] Fine-graded dense resin concrete is composed of high-toughness resin adhesive, mineral aggregate, fiber and slow-release anti-icing agent; according to the weight ratio, high-toughness resin adhesive is 4.8 parts, coarse aggregate is 78 parts, fine aggregate is 6 parts, slaked lime powder is 2.3 parts, polyester fiber is 0.3 parts, and slow-release anti-icing agent is 5 parts; the wearing layer mineral material is composed of steel slag coarse aggregate, limestone fine aggregate, and slaked lime powder. Stir at a speed of 65 rpm for 4 minutes at room temperature, spread evenly at a thickness of 3 cm, and flatten and compact for 9 times.

[0061] The polymer resin consists of 82 parts of high-toughness resin, 13 parts of alicyclic polyamine curing agent, and 9 parts of anti-aging agent. The coating amount is controlled at 1.2kg / m 2 The wear-resistant aggregate is a mixture of 15 parts of oil-free steel slag, 20 parts of high-strength quartz sand, and 75 parts of basalt particles. The particle size range is 3.5mm. After one day of natural curing, the resin concrete functional wear layer is paved.

[0062] Example 2

[0063] like Figure 1 A rivet-free lane-level combined ultra-high performance concrete pavement structure is shown, with a total thickness of 8.8 cm, comprising a 4 mm rivet-free composite bonding layer 1, a 4 cm unreinforced ultra-tough cement concrete pavement layer 2, a 4 mm shear-resistant bonding layer 3 and a 4 cm resin concrete functional wear layer 4, which are sequentially arranged on a steel panel base 0 from bottom to top;

[0064] like Figure 2 and Figure 3 There is a construction joint between the unreinforced super-tough cement concrete pavement layer 2 and the original pavement 5. The unreinforced super-tough cement concrete pavement layer 2 and the resin concrete functional wear layer 4 are staggered in a tongue-and-groove joint structure with a spacing of 25 cm. The bevel of the tongue-and-groove joint avoids the wheel track position. The construction joint interface is coated with a high-strength interface agent with a coating amount of 1.5 kg / m 2 .

[0065] A method for preparing a rivet-free lane-level combined ultra-high performance concrete pavement structure, calculated by mass fraction, comprises the following steps:

[0066] S1. The steel panel is sandblasted to remove rust and clean, and a steel panel base with a cleanliness level of Sa2.5 or above and a roughness of 145μm is obtained;

[0067] S2. After sandblasting and rust removal, lay the rivet-free composite bonding layer within 3 hours, and evenly apply high-toughness epoxy resin on the surface of the steel panel at a dosage of 1.2kg / m 2 ; Then spread the gravel with a diameter of 4mm and a spreading amount of 4.5kg / m 2 , forming a rivet-free composite bonding layer; the high-toughness resin is composed of 48 parts of modified fatty amine curing agent, 45 parts of modified polyamide curing agent, and 2 parts of accelerator; the modified fatty amine curing agent is formed by heating reaction of 85 parts by weight of a first component and 16 parts by weight of a second component, the first component is an equal proportion of two of enamine or alkylamine or polyetheramine, and the second component is an epoxy resin or an active epoxy diluent.

[0068] The high-strength interface wet adhesive is composed of 76 parts of bisphenol A epoxy resin, 10 parts of ultrafine quartz powder, 6 parts of heavy-burned active calcium carbonate filler, 8 parts of polyester toughening agent, 16 parts of modified amine curing agent, 5 parts of liquid silica thixotropic agent, and 6 parts of propylene oxide phenyl ether diluent. The ultrafine quartz powder has a particle size of 250μm and the heavy-burned calcium carbonate has a particle size of 120μm. After the rivet-free composite wet adhesive layer is cured for 36 hours, the high-strength interface wet adhesive is manually rolled or mechanically sprayed on it, with a coating amount of 0.9kg / m 2 ;

[0069] S3. Within 100 minutes after the high-strength wet bonding interface agent is applied, the unreinforced super-tough cement concrete pavement layer is applied, and the transverse and longitudinal composite reinforcement mesh is arranged. The longitudinal reinforcement is arranged in the lower layer, and the transverse reinforcement is arranged in the upper layer. The transverse and longitudinal spacing is 95mm, and it is fixed by binding. The composite reinforcement is basalt fiber reinforcement, glass fiber reinforcement or carbon fiber reinforcement, with a diameter of 5mm. Then the unreinforced super-tough cement concrete pavement layer can be poured;

[0070] S4. Prepare ultra-high performance concrete according to the proportion of 12 parts of cementitious material, 10 parts of sand, 8 parts of coarse aggregate, 1.4 parts of water reducer, 220 parts of steel fiber, 1.8 parts of water, 0.45 parts of phase change material, and 0.4 parts of chloride ion curing agent; pave the ultra-high performance concrete on the rivet-free composite bonding layer, control the vibration interval to 0.8m, the vibration time at each location to 12s, perform surface calendering treatment before initial setting after vibration and compaction, and perform milling treatment on the surface after final setting to form tenons; the milling depth is 1.5 to 2.5cm, the exposed bone rate is 68%, and the exposed steel fiber rate is 71%, and then spray water mist and cover with film for moisturizing and curing for 14 days to form a high-density non-reinforced ultra-tough cement concrete pavement layer;

[0071] S5. After the maintenance of the unreinforced ultra-tough cement concrete pavement is completed, the floating slurry and loose debris on its surface are removed. There is a construction joint between the lane-level combined ultra-high performance concrete pavement and the original pavement. The upper and lower layers of the pavement are staggered, with a spacing of 18cm, and a tongue-and-groove joint structure. The tongue-and-groove joint is set with a trapezoidal mortise and tenon groove by milling. The opening width is 900mm, the bottom width is set to 500mm, and the distance between the mortise and tenon grooves is 1200mm. The high-strength interface agent is applied to the construction joint interface, and the coating amount is 1.5kg / m 2 ;

[0072] S6. Then prepare a high-toughness, strong-bonding, long-lasting shear-resistant bonding layer; mix 55 parts of modified fatty amine curing agent, 52 parts of modified polyamide curing agent, and 1.8 parts of accelerator; wherein the modified fatty amine curing agent is formed by heating and reacting 82 parts by weight of at least two of enamine, alkylamine, and polyetheramine and 16 parts by weight of epoxy resin and active epoxy diluent, and the coating amount is controlled to be 1.7kg / m 2 ;

[0073] S7. Lay the resin concrete functional wearing layer within 1 hour after applying the shear-resistant binder. The resin concrete functional wearing layer consists of fine-graded dense resin concrete, polymer resin and wear-resistant aggregate particles.

[0074] Fine-graded dense resin concrete is composed of high-toughness resin adhesive, mineral aggregate, fiber and slow-release anti-icing agent; according to the weight ratio, high-toughness resin adhesive is 5 parts, coarse aggregate is 78 parts, fine aggregate is 8 parts, slaked lime powder is 2 parts, polyester fiber is 0.35 parts, and slow-release anti-icing agent is 5 parts; the wearing layer mineral material is composed of steel slag coarse aggregate, limestone fine aggregate, and slaked lime powder. Stir at a speed of 65 rpm for 4 minutes at room temperature, spread evenly at a thickness of 4 cm, and flatten and compact for 9 times.

[0075] The polymer resin is composed of 82 parts of high-toughness resin, 14 parts of alicyclic polyamine curing agent, and 10 parts of anti-aging agent, with a controlled coating amount of 1.2kg / m2; the wear-resistant aggregate is a mixture of 18 parts of oil-free steel slag, 32 parts of high-strength quartz sand, and 68 parts of basalt particles, with a particle size range of 4mm. After 1d of natural curing, the resin concrete functional wear layer is paved.

[0076] Example 3

[0077] like Figure 1 A rivet-free lane-level combined ultra-high performance concrete pavement structure is shown, with a total thickness of 7 cm, comprising a 3 mm rivet-free composite bonding layer 1, a 3.5 cm unreinforced ultra-tough cement concrete pavement layer 2, a 2 mm shear-resistant bonding layer 3 and a 3 cm resin concrete functional wear layer 4, which are sequentially arranged on a steel panel base 0 from bottom to top;

[0078] like Figure 2 and Figure 3 There is a construction joint between the unreinforced super-tough cement concrete pavement layer 2 and the original pavement 5. The unreinforced super-tough cement concrete pavement layer 2 and the resin concrete functional wear layer 4 are staggered in a tongue-and-groove joint structure with a spacing of 28 cm. The bevel of the tongue-and-groove joint avoids the wheel track position. The construction joint interface is coated with a high-strength interface agent with a coating amount of 1.4 kg / m 2 .

[0079] A method for preparing a rivet-free lane-level combined ultra-high performance concrete pavement structure, calculated by mass fraction, comprises the following steps:

[0080] S1. The steel panel is sandblasted to remove rust and clean, and a steel panel base with a cleanliness level of Sa2.5 or above and a roughness of 120μm is obtained;

[0081] S2. After sandblasting and rust removal, lay the rivet-free composite bonding layer within 3 hours, and evenly apply high-toughness epoxy resin on the surface of the steel panel at a dosage of 1.2kg / m 2 ; Then spread the gravel with a diameter of 3.5mm and a spreading amount of 3.9kg / m 2 , forming a rivet-free composite bonding layer; the high-toughness resin is composed of 43 parts of modified fatty amine curing agent, 56 parts of modified polyamide curing agent, and 1.6 parts of accelerator; the modified fatty amine curing agent is formed by heating reaction of 88 parts by weight of a first component and 15 parts by weight of a second component, the first component is an equal proportion of two of enamine or alkylamine or polyetheramine, and the second component is an epoxy resin or an active epoxy diluent.

[0082] The high-strength interface wet adhesive is composed of 78 parts of bisphenol A epoxy resin, 10 parts of ultrafine quartz powder, 6 parts of heavy-burned active calcium carbonate filler, 10 parts of polyester toughening agent, 17 parts of modified amine curing agent, 5 parts of liquid silica thixotropic agent, and 8 parts of propylene oxide phenyl ether diluent. The ultrafine quartz powder has a particle size of 260μm and the heavy-burned calcium carbonate has a particle size of 135μm. After the rivet-free composite wet adhesive layer is cured for 24 hours, the high-strength interface wet adhesive is manually rolled or mechanically sprayed on it, with a coating amount of 1.2kg / m 2 ;

[0083] S3. Within 100 minutes after the high-strength wet bonding interface agent is applied, the non-reinforced super-tough cement concrete pavement layer is applied, and the transverse and longitudinal composite reinforcement mesh is arranged. The longitudinal reinforcement is arranged in the lower layer, and the transverse reinforcement is arranged in the upper layer. The transverse and longitudinal spacing is 70mm, and it is fixed by binding. The composite reinforcement is basalt fiber reinforcement, glass fiber reinforcement or carbon fiber reinforcement, with a diameter of 4.5mm. Then the non-reinforced super-tough cement concrete pavement layer can be poured;

[0084] S4. Prepare ultra-high performance concrete according to the proportion of 12 parts of cementitious material, 10 parts of sand, 6 parts of coarse aggregate, 0.4 parts of water reducer, 200 parts of steel fiber, 1.8 parts of water, 0.45 parts of phase change material, and 0.3 parts of chloride ion curing agent; pave the ultra-high performance concrete on the rivet-free composite bonding layer, control the vibration interval to 0.8m, the vibration time at each location to 18s, perform surface calendering treatment before initial setting after vibration and compaction, and perform milling treatment on the surface after final setting to form tenons; the milling depth is 1.5 to 2.5cm, the exposed bone rate is 66%, and the exposed steel fiber rate is 74%, and then spray water mist and cover with film for moisturizing and curing for 14 days to form a high-density non-reinforced ultra-tough cement concrete pavement layer;

[0085] S5. After the maintenance of the unreinforced ultra-tough cement concrete pavement is completed, the floating slurry and loose debris on its surface are removed. There is a construction joint between the lane-level combined ultra-high performance concrete pavement and the original pavement. The upper and lower layers of the pavement are staggered, with a spacing of 25cm, and a tongue-and-groove joint structure. The tongue-and-groove joint is set with a trapezoidal mortise and tenon groove by milling. The opening width is 850mm, the bottom width is set to 450mm, and the distance between the mortise and tenon grooves is 1300mm. The high-strength interface agent is applied to the construction joint interface, and the coating amount is 0.9kg / m 2 ;

[0086] S6. Then prepare a high-toughness, strong-bonding, long-lasting shear-resistant bonding layer; mix 52 parts of modified fatty amine curing agent, 48 parts of modified polyamide curing agent, and 1.6 parts of accelerator; wherein the modified fatty amine curing agent is formed by heating and reacting 88 parts by weight of at least two of enamine, alkylamine, and polyetheramine and 18 parts by weight of epoxy resin and active epoxy diluent, and the coating amount is controlled to be 1.8kg / m 2 ;

[0087] S7. Lay the resin concrete functional wearing layer within 1 hour after applying the shear-resistant binder. The resin concrete functional wearing layer consists of fine-graded dense resin concrete, polymer resin and wear-resistant aggregate particles.

[0088] Fine-graded dense resin concrete is composed of high-toughness resin adhesive, mineral aggregate, fiber and slow-release anti-icing agent; according to the weight ratio, high-toughness resin adhesive is 4.5 parts, coarse aggregate is 77 parts, fine aggregate is 8 parts, slaked lime powder is 1.5 parts, polyester fiber is 0.3 parts, and slow-release anti-icing agent is 3-6 parts; the wearing layer mineral material is composed of steel slag coarse aggregate, limestone fine aggregate, and slaked lime powder. Stir at a speed of 60 rpm for 4 minutes at room temperature, spread evenly at a thickness of 3 cm, and flatten and compact for 9 times.

[0089] The polymer resin is composed of 82 parts of high-toughness resin, 12 parts of alicyclic polyamine curing agent, and 8 parts of anti-aging agent, and the coating amount is controlled at 1.5kg / m2; the wear-resistant aggregate is mixed with 18 parts of oil-free steel slag, 20 parts of high-strength quartz sand, and 65 parts of basalt particles, with a particle size range of 3mm. After 1d of natural curing, the resin concrete functional wear layer is paved.

[0090] Comparative Example 1

[0091] A combined ultra-high performance concrete pavement structure, with a total thickness of 6.5 cm, comprising a 3 mm composite resin bonding layer 1, a 3.5 cm unreinforced ultra-tough cement concrete pavement layer 2, a 2 mm shear bonding layer 3 and a 2.5 cm resin concrete functional wear layer 4, which are sequentially arranged on a steel panel base 0 from bottom to top;

[0092] There is a construction joint between the unreinforced super-tough cement concrete pavement layer 2 and the original pavement 5, and the unreinforced super-tough cement concrete pavement layer 2 and the resin concrete functional wearing layer 4 are connected by conventional flat seams.

[0093] A method for preparing a rivet-free lane-level combined ultra-high performance concrete pavement structure, calculated by mass fraction, comprises the following steps:

[0094] S1. The steel panel is sandblasted to remove rust and clean, and a steel panel base with a cleanliness level of Sa2.5 or above and a roughness of 120μm is obtained;

[0095] S2. After sandblasting and rust removal, the composite resin bonding layer shall be laid within 3 hours. The high-toughness epoxy resin shall be evenly coated on the surface of the steel panel at a dosage of 1.5kg / m 2 ; Then spread the gravel with a diameter of 3.5mm and a spreading amount of 4kg / m 2, forming a rivet-free composite bonding layer; the high-toughness resin is composed of 45 parts of modified fatty amine curing agent, 45 parts of modified polyamide curing agent, and 1.5 parts of accelerator; the modified fatty amine curing agent is formed by heating reaction of 88 parts by weight of a first component and 12 parts by weight of a second component, the first component is an equal proportion of two of enamine or alkylamine or polyetheramine, and the second component is an epoxy resin or an active epoxy diluent.

[0096] S3. After the curing of the composite resin bonding layer is completed, the non-reinforced super-tough cement concrete pavement layer is applied, and the horizontal and vertical steel bars are arranged. The longitudinal bars are arranged in the lower layer, and the transverse bars are arranged in the upper layer. The horizontal and vertical spacing is 50mm, and the steel bars are fixed by binding. The diameter of the steel bars is 6mm. Then the non-reinforced super-tough cement concrete pavement layer can be poured;

[0097] S4. Prepare super-tough concrete according to the proportion of 9-13 parts of cementitious materials, 8-12 parts of sand, 4-9 parts of coarse aggregate, 0.3-0.5 parts of water reducing agent, 0.8-250 parts of steel fiber, 1.5-2 parts of water, 0.3-0.6 parts of phase change material, and 0.1-0.5 parts of chloride ion curing agent; pave the super-tough concrete on the composite bonding layer, control the vibration interval to 0.8m, the vibration time at each location to 18s, perform surface calendering treatment before initial setting after vibration and compaction, and perform milling treatment on the surface after final setting to form tenons; the milling depth is 1.5-2.5cm, the exposed bone rate is 66%, the exposed steel fiber rate is 72%, and then spray water mist and cover with film for moisture retention and curing for 14d to form a high-density non-reinforced super-tough cement concrete pavement layer;

[0098] S5. After the maintenance of the unreinforced ultra-tough cement concrete pavement is completed, the floating slurry and loose debris on its surface are removed. There is a construction joint between the lane-level combined ultra-high performance concrete pavement and the original pavement, and a conventional plane joint layout is adopted;

[0099] S6. Then prepare a high-toughness, strong-bonding, long-lasting shear-resistant bonding layer; mix 50 parts of modified fatty amine curing agent, 55 parts of modified polyamide curing agent, and 1.2 parts of accelerator; wherein the modified fatty amine curing agent is formed by heating and reacting 89 parts by weight of at least two of enamine, alkylamine, and polyetheramine and 18 parts by weight of epoxy resin and active epoxy diluent, and the coating amount is controlled to be 1.6kg / m 2 ;

[0100] S7. Within 1 hour after the shear binder is applied, the resin concrete functional wear layer is laid, which is composed of high-toughness resin adhesive, mineral aggregate, fiber and slow-release anti-icing agent; according to the weight ratio, the high-toughness resin adhesive is 5 parts, the coarse aggregate is 78 parts, the fine aggregate is 8 parts, the slaked lime powder is 2.5 parts, the polyester fiber is 0.3 parts, and the slow-release anti-icing agent is 5 parts; the wear layer mineral material is composed of steel slag coarse aggregate, limestone fine aggregate, and slaked lime powder. Stir at a speed of 66 rpm for 5 minutes at room temperature, spread evenly at a thickness of 2.5 cm, and compact it 9 times. After natural curing for 1 day, the resin concrete functional wear layer is laid.

[0101] Comparative Example 2

[0102] A rivet-free lane-level combined ultra-high performance concrete pavement structure, with a total thickness of 7.5 cm, comprising a 3 mm rivet-free composite bonding layer 1, a 4 cm unreinforced ultra-tough cement concrete pavement layer 2, a 2 mm shear-resistant bonding layer 3 and a 3 cm resin concrete functional wear layer 4, which are sequentially arranged on a steel panel base 0 from bottom to top;

[0103] There is a construction joint between the unreinforced super-tough cement concrete pavement layer 2 and the original pavement 5, and the unreinforced super-tough cement concrete pavement layer 2 and the resin concrete functional wearing layer 4 are arranged in a flat seam structure.

[0104] A method for preparing a rivet-free lane-level combined ultra-high performance concrete pavement structure, calculated by mass fraction, comprises the following steps:

[0105] S1. The steel panel is sandblasted to remove rust and clean, and a steel panel base with a cleanliness level of Sa2.5 or above and a roughness of 120μm is obtained;

[0106] S2. After sandblasting and rust removal, lay the rivet-free composite bonding layer within 3 hours, and evenly apply high-toughness epoxy resin on the surface of the steel panel at a dosage of 1.8kg / m 2 ; Then spread the gravel with a diameter of 4mm and a spreading amount of 4kg / m 2 , forming a rivet-free composite bonding layer; the high-toughness resin is composed of 48 parts of modified fatty amine curing agent, 52 parts of modified polyamide curing agent, and 1.2 parts of accelerator; the modified fatty amine curing agent is formed by heating reaction of 88 parts by weight of a first component and 12 parts by weight of a second component, the first component is an equal proportion of two of enamine or alkylamine or polyetheramine, and the second component is an epoxy resin or an active epoxy diluent.

[0107] S3. After the composite resin bonding layer is cured, the non-reinforced super-tough cement concrete pavement layer is applied, and the horizontal and vertical steel bars are arranged. The longitudinal bars are arranged in the lower layer, and the transverse bars are arranged in the upper layer. The horizontal and vertical spacing is 80mm, and the steel bars are fixed by binding. The diameter of the steel bars is 6mm. Then the non-reinforced super-tough cement concrete pavement layer can be poured;

[0108] S4. Prepare ultra-high performance concrete according to the proportion of 10 parts of cementitious material, 10 parts of sand, 8 parts of coarse aggregate, 0.4 parts of water reducer, 200 parts of steel fiber, 1.8 parts of water, 0.5 parts of phase change material, and 0.3 parts of chloride ion curing agent; pave the ultra-high performance concrete on the rivet-free composite bonding layer, control the vibration interval to 0.9m, and the vibration time at each location to 20s. After vibration and compaction, perform surface calendering before initial setting, and perform milling on the surface after final setting to form tenons; the milling depth is 1.2cm, the exposed bone rate is 70%, and the exposed steel fiber rate is 72%, and then spray water mist and cover with film for moisturizing and curing for 14d to form a high-density non-reinforced ultra-tough cement concrete pavement layer;

[0109] S5. After the maintenance of the unreinforced ultra-tough cement concrete pavement is completed, the floating slurry and loose debris on its surface are removed. There is a construction plane joint between the lane-level combined ultra-high performance concrete pavement and the original pavement, and the interface is polished;

[0110] S6. Then prepare a high-toughness, strong-bonding, long-lasting shear-resistant bonding layer; mix 56 parts of modified fatty amine curing agent, 42 parts of modified polyamide curing agent, and 1.2 parts of accelerator; wherein the modified fatty amine curing agent is formed by heating and reacting 88 parts by weight of at least two of enamine, alkylamine, and polyetheramine and 16 parts by weight of epoxy resin and active epoxy diluent, and the coating amount is controlled to be 1.6kg / m 2 ;

[0111] S7. Within 1 hour after the shear binder is applied, the resin concrete functional wear layer is laid, which is composed of high-toughness resin adhesive, mineral aggregate, fiber and slow-release anti-icing agent; according to the weight ratio, the high-toughness resin adhesive is 5 parts, the coarse aggregate is 78 parts, the fine aggregate is 6 parts, the slaked lime powder is 2 parts, the polyester fiber is 0.3 parts, and the slow-release anti-icing agent is 4 parts; the wear layer mineral material is composed of steel slag coarse aggregate, limestone fine aggregate, and slaked lime powder. Stir at a speed of 60 rpm for 4 minutes at room temperature, spread evenly at a thickness of 2.5 cm and compact it 8 times. After natural curing for 1 day, the resin concrete functional wear layer is laid.

[0112] Performance Verification

[0113] The various performance index parameters of the rivet-free lane-level combined ultra-high performance concrete pavement structure laid in the above-mentioned embodiment and comparative example and those in the comparative example are shown in the following table.

[0114]

[0115] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A rivet-free lane-level combined ultra-high performance concrete pavement structure, characterized in that: It includes a rivet-free composite bonding layer, a non-reinforced ultra-tough cement concrete pavement layer, a shear-resistant bonding layer and a resin concrete functional wear layer which are sequentially arranged on the steel panel base from bottom to top; The joint between the unreinforced super-tough cement concrete pavement layer and the original pavement is constructed in the form of a tongue-and-groove joint. The unreinforced super-tough cement concrete pavement layer and the resin concrete functional wear layer are staggered with a spacing of 10-30 cm, and the bevel of the tongue-and-groove joint avoids the wheel track position; a high-strength interface agent is applied to the construction joint interface with a coating amount of 0.2-1.6 kg / m 2 .

2. The rivet-free lane-level combined ultra-high performance concrete pavement structure according to claim 1 is characterized in that: The rivet-free composite bonding layer is composed of high-toughness resin, crushed stone and high-strength interface agent; wherein the high-toughness resin is 1-2 kg / m 2 Evenly apply on the surface of the steel panel; the diameter of the crushed stone is 1~5mm, and the spreading amount is 3~5kg / m 2 ; The coating amount of the high-strength interface agent is 0.5~1.5kg / m 2 The time interval between coating and pouring of new concrete is 0.5~2h.

3. The rivet-free lane-level combined ultra-high performance concrete pavement structure according to claim 2 is characterized in that: The high-toughness resin is composed of 40-60 parts of a modified fatty amine curing agent, 40-60 parts of a modified polyamide curing agent, and 1-2 parts of an accelerator; the modified fatty amine curing agent is formed by heating a first component of 80-90 parts by weight and a second component of 10-20 parts by weight, wherein the first component is an equal proportion of two of enamine, alkylamine, or polyetheramine, and the second component is an epoxy resin or an active epoxy diluent.

4. The rivet-free lane-level combined ultra-high performance concrete pavement structure according to claim 1 is characterized in that: The high-strength interface agent includes 70-80 parts of bisphenol A epoxy resin, 5-12 parts of ultrafine quartz powder, 5-8 parts of heavy-burned active calcium carbonate filler, 6-15 parts of polyester toughening agent, 10-18 parts of modified amine curing agent, 3-6 parts of liquid silicon dioxide thixotropic agent, and 4-10 parts of propylene oxide phenyl ether diluent, wherein the particle size of the ultrafine quartz powder is 50-350 μm, and the particle size of the heavy-burned calcium carbonate is 20-150 μm.

5. The rivet-free lane-level combined ultra-high performance concrete pavement structure according to claim 1 is characterized in that: The unreinforced ultra-tough cement concrete pavement layer is composed of gel material, sand, coarse aggregate, water reducer, fiber, water, phase change material and chloride ion curing agent, wherein the gel material is 9-13 parts, the sand is 8-12 parts, the coarse aggregate is 4-9 parts, the water reducer is 0.3-0.5 parts, the fiber is 0.8-2.5 parts, the water is 1.5-2 parts, the phase change material is 0.3-0.6 parts, and the chloride ion curing agent is 0.1-0.5 parts; the coarse aggregate includes crushed stone coarse aggregate and porous coarse aggregate, and the fiber is steel fiber or glass fiber or basalt fiber.

6. The rivet-free lane-level combined ultra-high performance concrete pavement structure according to claim 5 is characterized in that: The tongue-and-groove joint is provided with a mortise and tenon by milling. The mortise and tenon is trapezoidal, with an opening width of 800-1000 mm, a bottom width of 400-600 mm, and a spacing of 1000-1200 mm between the mortise and tenon. The milling depth is 1.5-2.5 cm, the exposed rate is 60%-70%, and the exposed rate of the fibers is 60%-75%.

7. The rivet-free lane-level combined ultra-high performance concrete pavement structure according to claim 3 is characterized in that: The shear-resistant bonding layer is composed of high-toughness resin and crushed stone, and the coating amount of the high-toughness resin is 1.2-2.5 kg / m 2 , crushed stone 2~4kg / m 2 Sprinkle evenly, cure for 2~4 hours, and then apply high-toughness resin for the second time at 0.8~1.5kg / m 2 The coating time and resin concrete construction time interval are 1~2 hours.

8. The rivet-free lane-level combined ultra-high performance concrete pavement structure according to claim 1 is characterized in that: The resin concrete functional wearing layer is composed of fine-graded dense resin concrete, polymer resin and wear-resistant aggregate particles; The fine-graded dense resin concrete is composed of high-toughness resin adhesive, mineral aggregate, fiber and slow-release anti-icing agent; the mineral aggregate is composed of steel slag coarse aggregate, limestone fine aggregate and slaked lime powder; the fiber is flocculent polyester fiber or basalt fiber, and the fiber length is 10mm~30mm; The polymer resin includes 75-85 parts of high-toughness resin, 10-15 parts of alicyclic polyamine curing agent, and 5-12 parts of anti-aging agent. The coating amount is controlled to be 1-2 kg / m 2 ; The wear-resistant aggregate is prepared by mixing 10-20 parts of oil-free steel slag, 15-35 parts of high-strength quartz sand, and 60-80 parts of basalt particles, with a particle size range of 1-5 mm.

9. The rivet-free lane-level combined ultra-high performance concrete pavement structure according to claim 1 is characterized in that: The total thickness of the pavement structure is 5~9cm, the thickness of the rivet-free composite bonding layer is 1~5mm; the thickness of the unreinforced super-tough cement concrete pavement layer is 3~5cm; the thickness of the shear-resistant bonding layer is 1~5mm; and the thickness of the resin concrete functional wear layer is 2~5cm.

10. The method for preparing a rivet-free lane-level combined ultra-high performance concrete pavement structure according to any one of claims 1 to 9, characterized in that: Calculated by mass, including the following steps: S1. The steel panel is subjected to sandblasting and rust removal cleaning treatment to obtain a steel panel base with a cleanliness level of Sa2.5 or above and a roughness of 60~150μm; S2. After sandblasting and rust removal, lay the rivet-free composite bonding layer within 3 hours, and evenly apply high-toughness epoxy resin on the surface of the steel panel at a dosage of 1~2kg / m 2 ; Then spread gravel with a diameter of 3~5mm and a spreading amount of 3~5kg / m 2 After curing for 12~24 hours, apply high-strength interface wet adhesive by manual rolling or mechanical spraying, with a coating amount of 0.5~1.5kg / m 2 , forming a rivet-free composite bonding layer; S3. Within 30 to 120 minutes after the high-strength wet bonding interface agent is applied, a non-reinforced super-tough cement concrete pavement layer is constructed, and a transverse and longitudinal composite reinforcement mesh is laid out, with longitudinal reinforcement arranged in the lower layer and transverse reinforcement arranged in the upper layer, with a transverse and longitudinal spacing of 35 to 100 mm, and fixed by binding. The composite reinforcement is basalt fiber reinforcement, glass fiber reinforcement or carbon fiber reinforcement, with a diameter of 3 to 6 mm; S4. Prepare super-tough cement concrete according to the proportion; pave the super-tough cement concrete on the rivet-free composite bonding layer, control the vibration interval to 0.5~1.0m, and the vibration time at each location to 10~20s. After vibration and compaction, perform surface calendering before initial setting, and perform surface milling after final setting to form tenons; then spray water mist and cover with film for moisturizing and curing for 14 days to form a high-density non-reinforced super-tough cement concrete pavement layer; S5. After the maintenance of the unreinforced super-tough cement concrete pavement is completed, the floating slurry and loose debris on its surface are removed. The unreinforced super-tough cement concrete pavement and the original pavement are constructed with a tongue-and-groove joint structure. The unreinforced super-tough cement concrete pavement and the resin concrete functional wear layer are staggered. The construction joint interface is coated with a high-strength interface agent with a coating amount of 0.2-1.6 kg / m 2 ; S6. Then prepare a high-toughness, strong-bonding, long-lasting shear-resistant bonding layer; 1.2~2.5kg / m 2 Apply high-toughness resin, then 2~4kg / m 2 Spread the gravel evenly, and after curing for 2-4 hours, apply a second coat of high-toughness resin at 0.8-1.5kg / m 2 ; S7. Lay the resin concrete functional wear layer within 1 hour of the second high-toughness resin coating, prepare the resin concrete mixture according to the proportion, spread it evenly in a thickness of 2 to 5 cm, and compact it flatly for 8 to 10 times. After natural curing for 1 day, the paving of the resin concrete functional wear layer is completed.

Citation Information

Cited By

  • High polymer elastic and toughened seamless expansion joint structure and preparation method thereof

    CN120465365A

  • Construction method for repairing airport pavement and sandwich composite structure

    CN121047176A